Social networks, household entrepreneurship, and relative poverty in rural China: the role of information access and informal funding - Xin Ding; Ehsan Elahi (Humanities & Social Sciences Communications)
Abstract This study examines how social networks and household entrepreneurship influence relative poverty among rural farming households in China. Using data from the China Household Tracking Survey and employing logit regression models with instrumental variables, the study analyzes direct and indirect pathways through which social networks affect poverty reduction. The findings reveal that social networks significantly reduce relative poverty in rural areas by improving three key dimensions: household income, living standards, and social security. Furthermore, social networks contribute to poverty reduction through two distinct mechanisms: enhancing farmers’ access to information and facilitating informal financing opportunities, promoting household entrepreneurship. Heterogeneity analysis indicates that social networks’ effectiveness varies across demographic groups, with stronger poverty reduction effects observed in male-headed households and those with lower education levels. These findings have important policy implications for rural poverty alleviation programs in China. Strengthening social networks through digital platforms and community organizations could enhance entrepreneurial opportunities and reduce poverty. Moreover, targeted support for female-headed households and improved access to informal financing channels could help maximize the poverty-reducing benefits of social networks in rural communities.